Optical-conductivity sum rule in cuprates and unconventional charge density waves: a short review - Benfatto, L.; Sharapov, S.G. (Физика низких температур, 2006)
We begin with an overview of the experimental results for the temperature and doping
dependences of the optical-conductivity spectral weight in cuprate superconductors across the
whole phase diagram. Then we discuss recent attempts to explain the observed behavior of the
spectral weight using reduced and full models with unconventional dx₂₋y₂
charge-density waves.